More than walls: Fear of crime in neighbourhoods with different poverty levels bordering gated communities. The Greater Metropolitan Area of Costa Rica - Barrantes Chaves, Karla (2024)
Urbanisation patterns in Central America have rapidly changed from open neighbourhoods to gated communities. Fear of crime is one of the leading motivations for gating; a common assumption is that residents protect themselves from the outside. This research argues that gated communities also affect those living outside their gates in the adjacent neighbourhoods. This qualitative research examines the Greater Metropolitan Area of Costa Rica through eight case studies, open neighbourhoods from extreme to zero poverty located next to gated communities. Data were collected through walks, focus groups, in-depth interviews and observations; a comparative structure of the eight case studies was done through thematic analysis. The findings suggest that physical and symbolic barriers exacerbate fear of crime for those outside the gate; non- porous edges affect mainly neighbourhoods in serious, moderate and mild poverty; however, effects of intangible boundaries such as exclusion are more substantial in those in extreme, serious and moderate poverty. This work concludes that local planning policies normalise gating, resulting in disparities in infrastructure and fear of others. Furthermore, gated communities help to fuel the feedback loop of fear of crime, as they might intensify fear towards the outside but receive nurture from it simultaneously.